Incommensurate counterrotating magnetic order stabilized by Kitaev interactions in the layered honeycomb $α$-Li$_2$IrO$_3$ - Williams, S; Johnson, R; Freund, F; Choi, S; Jesche, A; Kimchi, I; Manni, S; Bombardi, A; Manuel, P; Gegenwart, P; Coldea, R (American Physical Society, 2016)
The layered honeycomb magnet α-Li2IrO3 has been theoretically proposed as a candidate to display unconventional magnetic behaviour associated with Kitaev interactions between spin-orbit entangled jeff = 1=2 magnetic moments on a honeycomb lattice. Here we report single crystal magnetic resonant x-ray diffraction combined with powder magnetic neutron diffraction to reveal an incommensurate magnetic order in the honeycomb layers with Ir magnetic moments counterrotating on nearest-neighbor sites. This unexpected type of magnetic structure for a honeycomb magnet cannot be explained by a spin Hamiltonian with dominant isotropic (Heisenberg) couplings. The magnetic structure shares many key features with the magnetic order in the structural polytypes β-and γ-Li2IrO3, understood theoretically to be stabilized by dominant Kitaev interactions between Ir moments located on the vertices of three-dimensional hyperhoneycomb and stripyhoneycomb lattices, respectively. Based on this analogy and a theoretical soft-spin analysis of magnetic ground states for candidate spin Hamiltonians, we propose that Kitaev interactions also dominate in α-Li2IrO3, indicative of universal Kitaev physics across all three members of the harmonic honeycomb family of Li2IrO3 polytypes.